Rapunzel syndrome presenting as acute pancreatitis, hypoproteinaemia and subsequent distal intestinal obstruction - Kavinda Dayasiri; Astor Rodrigues; Alex Lee (Elsevier, 2020)
Rapunzel syndrome is a rare presentation of trichobezoar and always occurs in patients who have a preceding history of trichophagia with or without trichotillomania. These patients are mostly female and present acutely with abdominal pain and vomiting. Acute pancreatitis and hypoproteinaemia are rare but life threatening presentations of Rapunzel syndrome which demands early diagnosis and management, however our case was unique as she also went on to develop distal intestinal obstruction caused by detachment of the trichobezoar. It is important that Rapunzel syndrome is considered in the differential diagnosis, especially in female patients with acute onset abdominal pain and vomiting with no clear explanation. As in our and other reported patients presenting with acute pancreatitis, underlying trichophagia was not initially evident and the history needed revisiting in order to confirm the diagnosis. Following acute management, it is crucial that all patients are followed up with psychological/psychiatric support and if indicated, upper GI endoscopy to exclude recurrence.